MENINGKATKAN PRODUKTIVITAS TANAMAN PAKAN MELALUI SISTEM TANAM GANDA - Nyimas Popi; Yuyun Yuwariah; Ana Rochana; Herryawan K.M.; Mansyur Mansyur (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2016)
Agricultural and forage land used are generally not increased even tends to decrease, therefore the land use needs to be optimized; one of them is by mean of multiple cropping system. Land management efforts through the multiple cropping systems selected is supporting the fertility of soil physical, chemical and biological. Multiple cropping systems require an appropriate plant species and a supportive environment to produce high-quality crops and availability of feed crops are sufficient throughout the year. Application of Multiple cropping system can increase the efficiency of environmental factors (sun, water and nutrients), inhibits the growth of weeds, suppress pests and diseases, save labor and improve the income of livestock farmers.Keywords: forage crops, multiple cropping systems, soil fertility